1999
DOI: 10.1074/jbc.274.47.33235
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiomyopathy and Lens Cataract Mutation in αB-crystallin Alters Its Protein Structure, Chaperone Activity, and Interaction with Intermediate Filaments in Vitro

Abstract: . (1999) 'The cardiomyopathy and lens cataract mutation in B-crystallin alters its protein structure, chaperone activity, and interaction withintermediate laments in vitro.', Journal of biological chemistry., 274 (47). pp. 33235-33243. Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
151
0
6

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(168 citation statements)
references
References 59 publications
(73 reference statements)
11
151
0
6
Order By: Relevance
“…First, in pulse-chase experiments, newly synthesized ezrin incorporated in Triton-insoluble complexes with keratins very rapidly (Ͻ10 min) and transiently ( Figure 6B). It is recognized, however, that coimmunoprecipitation of newly synthesized ezrin with IFs might be mediated by other proteins such as, for example, IF-associated chaperones (Perng et al, 1999). The second line of evidence showed that dormant, but not active, ezrin can bind directly to keratins in vitro ( Figure 7, B and C).…”
Section: Discussionmentioning
confidence: 96%
“…First, in pulse-chase experiments, newly synthesized ezrin incorporated in Triton-insoluble complexes with keratins very rapidly (Ͻ10 min) and transiently ( Figure 6B). It is recognized, however, that coimmunoprecipitation of newly synthesized ezrin with IFs might be mediated by other proteins such as, for example, IF-associated chaperones (Perng et al, 1999). The second line of evidence showed that dormant, but not active, ezrin can bind directly to keratins in vitro ( Figure 7, B and C).…”
Section: Discussionmentioning
confidence: 96%
“…72 An in vitro chaperone assay demonstrated that the mutant p.Arg120Gly alphaB-crystallin becomes functionally deficient. 89 Expression of the mutant alphaB-crystallin in SW13 and BHK21 cells leads to formation of abnormal aggregates that contain both desmin and alphaB-crystallin. 8 Transgenic mice expressing mutant alphaB crystallin show the presence of abnormal desmin and alphaB-crystallin aggregates in the cardiomyocytes; formation of aggregates is the result of the loss of protection from alphaBcrystallin.…”
Section: Role Of Alphab-crystallinmentioning
confidence: 99%
“…The wild type ␣B-crystallin, K174X and A171X proteins were prepared essentially as described (29), but adding polyethyleneimine (final concentration 0.1% (w/v)) to remove contaminating DNA (10,30) before purification by ion exchange chromatography on a Fractogel TMAE column. Peak fractions were pooled and then dialyzed into 20 mM Tris-HCl, 100 mM NaCl, pH 7.4, in preparation for size exclusion chromatography on a Fractogel EMD BioSEC Superformance column (60 ϫ 1.6 cm; VWR, UK).…”
Section: Protein Expression and Purification Of ␣B-crystallin Mutantsmentioning
confidence: 99%